Mycofabrication of selenium and tellurium nanoparticles by using Penicillium rubens: In-vitro physicochemical, antimicrobial, antioxidant, urease inhibitory, thrombolytic and anticoagulant performance - Hamed Barabadi; Fatemeh Ashouri; Kamyar Jounaki; Reza Jahani; Salimeh Amidi; Omid Hosseini; Melika Kamali (Nanomedicine Journal)
Objective(s): This study aimed to investigate the extracellular synthesis of colloidal nanosized selenium (SeNPs) and tellurium (TeNPs) particles using the supernatant of Penicillium rubens, and to evaluate their biological activities.Materials and Methods: Colloidal SeNPs and TeNPs were characterized using energy-dispersive X-ray spectroscopy (EDX), field emission scanning electron microscopy (FE-SEM), dynamic light scattering (DLS), and Fourier transform infrared spectroscopy (FT-IR) analysis. Biological tests included antimicrobial tests using the well diffusion assay, broth microdilution assay, and flow cytometry, as well as antioxidant, urease inhibitory, thrombolytic, and anticoagulant assays.Results: The average hydrodynamic diameters of the synthesized SeNPs and TeNPs were determined to be 43.91 nm and 37.17 nm, respectively. TeNPs exhibited significant antibacterial activity against Escherichia coli with an inhibition zone (IZ) of 27 mm and a minimum inhibition concentration (MIC) of 2.5 mg.mL-1. Flow cytometry analysis showed a dose-dependent bacterial cell death with TeNPs. However, SeNPs did not display any antibacterial activity against Escherichia coli. Neither TeNPs nor SeNPs showed antimicrobial properties against Staphylococcus aureus and Candida albicans. Both TeNPs and SeNPs exhibited antioxidant properties, inhibiting 43.90±1.98% and 57.93±2.20% of DPPH free radicals at 1 mg.mL-1, respectively. Additionally, the mycofabricated NPs displayed a dose-dependent urease inhibitory activity with maximum inhibition of 63.81±1.69% and 46.95±3.39% at 1 mg.mL-1, respectively. However, neither TeNPs nor SeNPs showed thrombolytic or anticoagulant activity at 1 mg.mL-1.Conclusion: Our findings demonstrate that mycofabricated nanosized selenium and tellurium particles possess significant antioxidant and urease inhibitory properties, with TeNPs showing promising antibacterial activity against E. coli. These results suggest potential applications for these nanoparticles in biomedical and agricultural fields.